Explain the development of social capital in urban water crisis management using factor analysis method (Case study: Karaj city) - khadigeh khatiri; iran ghazi; nemat hasani (تحقیقات کاربردی علوم جغرافیایی)
Identifying the level and trend of social capital among the people of a society can help to identify the social and cultural changes of that. The purpose of this study is to explain the development of social capital in urban water crisis management using factor analysis. This research is of applied-developmental type and descriptive-survey study method. The questionnaire is used to collect information and SPSS software and exploratory analysis statistical test is used to analyze the data. The statistical population includes the countrychr('39')s crisis and water supply managers (15 people chosen by targeted sampling); Also, all residents of Karaj during 1396 - 1395, which was used as a statistical sample using the Cochranchr('39')s table for 350 people, of which 44.3% were women and 55.7% were men. The results of statistical analysis showed that in people (sampled) of statistical population’s opinion the level of social capital was lower than what desired. Also, the factors involved in the development of social capital for the water shortage crisis were counted and measured in the form of 24 variables. And finally 5 items eliminated to be effective ones to development of social capital in crisis management of urban water which are ( in order of preferences ) social trust, motivating policies, change in attitude atmosphere, infrastructures of interactions and values in the society, mutual reconciliation between people and government